2004
DOI: 10.1177/0273475304268779
|View full text |Cite
|
Sign up to set email alerts
|

Academic Integrity in the Business School Environment: I’ll Get by with a Little Help from My Friends

Abstract: The incidence of academic dishonesty has been increasing throughout the past few decades. Past research has indicated that business students cheat more than their peers in other disciplines across the university. And, of particular concern to marketing educators, the current research finds that marketing majors cheat significantly more than their peers in other business disciplines. The research results also indicate that students are much more likely to cheat in situations in which friends (versus mere acquai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
117
2
15

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 148 publications
(160 citation statements)
references
References 31 publications
6
117
2
15
Order By: Relevance
“…In congruence with previous research (e.g., Jordan, 2001), Chapman et al (2004) found that the phenomenon of peer perception is common regarding cheating. For instance, while only 26% of students reported having stolen an exam, 92% expected their peers to have done so.…”
Section: General Predictorssupporting
confidence: 90%
See 4 more Smart Citations
“…In congruence with previous research (e.g., Jordan, 2001), Chapman et al (2004) found that the phenomenon of peer perception is common regarding cheating. For instance, while only 26% of students reported having stolen an exam, 92% expected their peers to have done so.…”
Section: General Predictorssupporting
confidence: 90%
“…Leming (1980) suggested that academic dishonesty is situation-specific and that its likelihood decreased in high risk situations. McCabe and Trevino (1997) discussed multiple personal and contextual variables that may contribute to whether or not a student will engage in such behavior, as did Chapman, Davis, Toy, and Wright (2004);DeBruin and Rudnick (2007); and Williams and Janosik (2007). Sometimes motivations, peer perception, and policy can influence students, as Jordan (2001) found, and at other times, the type of work assigned can elicit a desire to cheat (Passow, Mayew, Finelli, Harding, & Carpenter, 2006).…”
Section: Literature Summarymentioning
confidence: 99%
See 3 more Smart Citations